The Influence of Digital Marketing, Product Innovation, and Brand Image on Consumer Purchasing Decisions for Ayam Geprek Cendrawasih in Situbondo - Abdurahman; Dassucik; Ahmad Hafas Rasyidi (Danadyaksa: Post Modern Economy Journal, 2026)
This study aims to examine the influence of digital marketing, product innovation, and brand image on consumers' purchasing decisions. The study adopted a quantitative approach using a Likert scale measurement. The population consisted of all consumers who had purchased and dined at Ayam Geprek Cendrawasih in Situbondo, although the exact population size was unknown. Data were collected through questionnaires measured using a Likert scale and analyzed with SPSS version 23. Based on the results of the F-test, the calculated F-value (F = 46.439) was greater than the F-table value (df1 = k − 1 = 4 − 1 = 3; df2 = n − k = 100 − 4 = 96; F-table = 2.699), indicating that Fcalculated > Ftable. Furthermore, the significance probability was lower than 0.05 (0.000 < 0.05). Therefore, H4 was accepted, indicating that digital marketing (X1), product innovation (X2), and brand image (X3) simultaneously have a positive and significant effect on consumers' purchasing decisions (Y). The results also showed that the calculated test statistic (46.493) exceeded the critical value (2.70), confirming that digital marketing, product innovation, and brand image significantly influence consumers' purchasing decisions. The adjusted R-square value was 0.579 (57.9%), indicating that digital marketing, product innovation, and brand image collectively explained 57.9% of the variance in consumers' purchasing decisions. The remaining 42.1% was influenced by other factors that were not examined in this study.